Antimalarials may reduce cancer risk in patients with systemic lupus erythematosus: a systematic review and meta-analysis of prospective studies - Xian-Bao Li; Nv-Wei Cao; Xiu-Jie Chu; Hao-Yue Zhou; Hua Wang; Si-Jie Yu; Dong-Qing Ye; Bao-Zhu Li (Annals of Medicine, 2021)
AbstractObjective To investigate the effect of antimalarials on cancer risk in patients with systemic lupus erythematosus (SLE).Methods PubMed, EMBASE, Web of Science, and the Cochrane Library were searched from their inception to October 3, 2020. Relative risk (RR) with 95% confidence intervals (CI) was used to evaluate the results. Subgroup analyses were used to assess heterogeneity. A funnel plot was used to explore publication bias. STATA was applied for all analyses.Results A total of nine studies consisted of four nested case–control, two case–cohort and three cohort studies were included. The results showed that antimalarials might reduce the risk of cancer in SLE (RR = 0.68, 95%CI: 0.55–0.85). In the subgroup analysis of four nested case–control and two case–cohort studies, the pooled RR was estimated as 0.69 (95% CI: 0.60–0.80). In four studies about hydroxychloroquine, the pooled RR was estimated as 0.70 (95% CI: 0.53–0.93). Antimalarials might reduce the risk of cancer in SLE among the Asian population (RR = 0.66; 95% CI: 0.49–0.88) (I2 = 43.1%, p = .173). And the consistent result was also found in SLE from multiple centres (RR = 0.72; 95%CI: 0.60–0.87) (I2 = 0%, p = .671). On disease course- and comorbidities-matched studies, the pooled RRs were 0.69 (95% CI: 0.52–0.93) and 0.59 (95% CI: 0.46–0.75), respectively.Conclusion Results of this meta-analysis showed that antimalarial drugs might be protective factors for cancer in SLE. Hydroxychloroquine might be a protective factor for cancer in SLE patients.KEY MESSAGESAntimalarials might be protective factors for cancer in SLE.Hydroxychloroquine might be a protective factor for cancer in SLE patients.The first article to perform the meta-analysis of antimalarial drugs on the risk of cancer in SLE patients.